1974
DOI: 10.1084/jem.140.3.764
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunity to Herpes Simplex Virus Mediated by Interferon

Abstract: Several lines of evidence suggest that cellular immunity plays an important role in the defense against herpes simplex virus (HSV) l infections. First, HSV can persist both in vivo and in vitro despite the presence of high concentrations of neutralizing antibody (1). Second, HSV infections are more severe in patients with deficiencies in cellular immunity (2-4). Third, experimental suppression of the cellular immune response makes animals more susceptible to HSV infection (2, 4). The precise way by which cell-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 23 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…
It has been shown that T cell-mediated immunity plays a major role (4,5,(7)(8)(9)(10)12) in control of and recovery from herpes simplex virus (HSV) infection. Nevertheless, the mechanism of immune T cell-mediated protection in vivo is complex and poorly understood.

Recent studies have revealed that peripheral T cells express different Lytalloantigens on their surfaces and are divisible into three subpopulations with phenotypes Lyt-1.2.3, Lyt-l, and Lyt-2.3 (2).

…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
It has been shown that T cell-mediated immunity plays a major role (4,5,(7)(8)(9)(10)12) in control of and recovery from herpes simplex virus (HSV) infection. Nevertheless, the mechanism of immune T cell-mediated protection in vivo is complex and poorly understood.

Recent studies have revealed that peripheral T cells express different Lytalloantigens on their surfaces and are divisible into three subpopulations with phenotypes Lyt-1.2.3, Lyt-l, and Lyt-2.3 (2).

…”
mentioning
confidence: 99%
“…It has been shown that T cell-mediated immunity plays a major role (4,5,(7)(8)(9)(10)12) in control of and recovery from herpes simplex virus (HSV) infection. Nevertheless, the mechanism of immune T cell-mediated protection in vivo is complex and poorly understood.…”
mentioning
confidence: 99%
“…Thus, not only could viral replication be triggered or be enhanced by cyclic nucleotide changes, but also the antiviral, activity of IFN on HSV could be suppressed. The spread of the herpesviruses to contiguous uninfected cells, which has been shown to be influenced by IFN (14), might then be affected.…”
Section: Discussionmentioning
confidence: 98%
“…Interferon was shown by Lodmell and Notkins [73] to be produced by rabbit leukocytes sensitized to PPD and stimulated with PPD or by leukocytes sensitized and then stimulated by HSV. Peritoneal exudate cells were more effective than spleen cells in each case, suggesting that macrophages were important in the response.…”
Section: Lymphocyte Interferon Productionmentioning
confidence: 97%